Identification of N7-methylguanosine-related IncRNA signature as a potential predictive biomarker for colon adenocarcinoma - Ma, Xiaomei; Yang, Baoshun; Yang, Yuan; Wu, Guozhi; Ma, Xiaoli; Yu, Xiao; Li, Yingwen; Wang, Yuping; Guo, Qinghong (Frontiers in Genetics, 2022)
N7-Methylguanosine (m7G) is an RNA modification serving as a key part of colon cancer development. Thus, a comprehensive analysis was executed to explore prognostic roles and associations with the immune status of the m7G-related lncRNA (m7G-RNAs) in colon adenocarcinoma (COAD). Identification of m7G-RNAs was achieved via Pearson’s correlation analysis of lncRNAs in the TCGA-COAD dataset and m7G regulators. A prognostic signature was developed via LASSO analyses. ESTIMATE, CIBERSORT, and ssGSEA algorithms were utilized to assess immune infiltration between different risk groups. Survival analysis suggested the high-risk group possesses poor outcomes compared with the low-risk group. According to the ROC curves, the m7G-RNAs signature exhibited a reliable capability of prediction (AUCs at 1, 3, and 5 years were 0.770, 0.766, and 0.849, respectively). Multivariate hazard analysis proved that the signature was an independent predictive indicator for OS. Moreover, the risk score was related to infiltration levels of naïve B cells, CD4+ memory T cells, and resting NK cells. The result revealed the prognostic value of m7G modification in COAD and provided a novel perspective on personalized immunotherapy strategies.